Manajemen Tatalaksana Kanker Kolorektal - M. Rizki Fazrian Danu; M. Sayuti (Pusat Riset dan Inovasi Nasional, 2023)
According to available data, colorectal cancer (CRC) is one of the most common malignant neoplasms. Depending on location, type of cancer, or gender, this disease ranks 2nd to 4th in terms of worldwide incidence. CRC from year to year shows an increasing trend both in terms of morbidity and mortality. Many factors may be responsible for the development of this disease, including genetic and environmental factors. Although CRC-related mortality is very high in high-income countries, CRC-related incidence and mortality is also increasing in developing countries. CRC that is detected early is completely curable with surgery and subsequent treatment. However, the recurrence rate is high, and cancer drug resistance increases the treatment failure rate. Access to early diagnosis and treatment of CRC for survival is somewhat possible in developed countries. However, these facilities are rarely available in developing countries.